Asymmetric labor market institutions in the EMU and the volatility of inflation and unemployment differentials - Mirko Abbritti; Andreas I. Mueller (Institute for the Study of Labor (IZA), 2012)
How does the asymmetry of labor market institutions affect the adjustment of a currency union to shocks? To answer this question, this paper sets up a dynamic currency union model with monopolistic competition and sticky prices, hiring frictions and real wage rigidities. In our analysis, we focus on the differentials in inflation and unemployment between countries, as they directly reflect how the currency union responds to shocks. We highlight the following three results: First, we show that it is important to distinguish between different labor market rigidities as they have opposite effects on inflation and unemployment differentials. Second, we find that asymmetries in labor market structures tend to increase the volatility of both inflation and unemployment differentials. Finally, we show that it is important to take into account the interaction between different types of labor market rigidities. Overall, our results suggest that asymmetries in labor market structures worsen the adjustment of a currency union to shocks.
urn:nbn:de:101:1-2012080812313
Keywords: E32; E52; F41; 330; currency union; labor market frictions; real wage rigidities; unemployment; sticky prices; inflation differentials; Währungsunion; Europäische Wirtschafts- und Währungsunion; Schock; Inflation; Arbeitslosigkeit; Volatilität; Arbeitsmarktflexibilität; Lohnrigidität; Preisrigidität; Theorie; EU-Staaten